The role of IL18-607C > A and IL18-137G > C promoter polymorphisms in antidepressant treatment phenotypes: A preliminary report. (27th May 2016) - Santos, Marlene; Carvalho, Serafim; Lima, Luís; Mota-Pereira, Jorge; Pimentel, Paulo; Maia, Dulce; Correia, Diana; Gomes, Sofia; Cruz, Agostinho; Medeiros, Rui
Highlights: IL18-607C   >   A and IL18-137G   >   C polymorphisms were associated with the risk of depression relapse. IL18 peripheral mRNA levels were found upregulated in IL18-607 CA/AA carriers. No association was found between SNPs and the development of TRD. Abstract: Recent studies suggest that immune activation and cytokines, such as IL-18, are involved in depression. IL-18 is expressed in brain and is increased in patients with moderate to severe depression. In this study we aim to evaluate the role of IL18-607C   >   A and IL18-137G   >   C promoter polymorphisms in antidepressant treatment phenotypes, specifically relapse and treatment resistant depression (TRD). We genotyped the referred polymorphisms in a subset of 80 MDD patients followed at Hospital Magalhães Lemos, Portugal, within a period of 27 months. Patients carrying IL18-607 CA or AA genotypes were significantly more prone to relapse after AD treatment and present a significantly lower time to relapse than patients carrying CC genotype. Similarly, patients carrying IL18-137 GC or CC genotypes have a significantly higher risk of relapse and display relapse significantly earlier than the ones carrying GG genotype. Due to the low number of IL18-607 CC and IL18-137 GG in the relapse subgroup (n = 3 and n = 5, respectively), results were validated by bootstrapping analysis, and remained significant. No association was found between the evaluated genetic polymorphisms and TRD. IL18 peripheral mRNA levels were upregulated in IL18-607 CA or AA carriers. This preliminary report indicates that IL18-607C   >   A and IL18-137G   >   C genetic polymorphisms seem to influence depression relapse after antidepressant treatment in our subset of depressed patients, and may possibly contribute to the disregulated IL-18 levels found in patients with depression.